2003
DOI: 10.1093/ajcn/77.5.1146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fatty acids and carbohydrates on the ratio of serum total to HDL cholesterol and on serum lipids and apolipoproteins: a meta-analysis of 60 controlled trials

Abstract: The effects of dietary fats on total:HDL cholesterol may differ markedly from their effects on LDL. The effects of fats on these risk markers should not in themselves be considered to reflect changes in risk but should be confirmed by prospective observational studies or clinical trials. By that standard, risk is reduced most effectively when trans fatty acids and saturated fatty acids are replaced with cis unsaturated fatty acids. The effects of carbohydrates and of lauric acid-rich fats on CAD risk remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

82
1,868
12
108

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,405 publications
(2,070 citation statements)
references
References 106 publications
82
1,868
12
108
Order By: Relevance
“…The composition of their saturated and polyunsaturated FA met the recommendations of the European Food Safety Authority (2010) and the French Nutrition Society (Legrand et al, 2001), that is, a value of n-6 PUFA : n-3 PUFA ratio lower than 5 and a limited level of 16 : 0, a proatherogenic FA, compared with 18:0, which seems to favour the prevention of cardiovascular disease (Mensink et al, 2003;Seidel et al, 2005;Tholstrup, 2005). The higher proportion of 18 : 0 in meat FA from organically reared pasture-fed lambs could be explained by a higher rumen bio-hydrogenation of dietary PUFA.…”
Section: Discussionmentioning
confidence: 57%
“…The composition of their saturated and polyunsaturated FA met the recommendations of the European Food Safety Authority (2010) and the French Nutrition Society (Legrand et al, 2001), that is, a value of n-6 PUFA : n-3 PUFA ratio lower than 5 and a limited level of 16 : 0, a proatherogenic FA, compared with 18:0, which seems to favour the prevention of cardiovascular disease (Mensink et al, 2003;Seidel et al, 2005;Tholstrup, 2005). The higher proportion of 18 : 0 in meat FA from organically reared pasture-fed lambs could be explained by a higher rumen bio-hydrogenation of dietary PUFA.…”
Section: Discussionmentioning
confidence: 57%
“…The effect of LA on ischemic stroke may act through several mechanisms. Numerous studies have thus reported a beneficial effect of LA on blood lipids and blood pressure 23, 24. Since hypercholesterolemia and hypertension have a different impact on the large precerebral arteries and the small cerebral arteries,9, 25, 26 this could partly explain the observed differences in risk between subtypes of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent meta-analysis of Mensink et al (2003) concluded that the overall effect of these FA on cardiovascular disease risk is neutral. The same review concluded that 16:0 had an overall negative effect, and in the present study this decreased with increasing MS inclusion.…”
Section: --mentioning
confidence: 99%